2018
DOI: 10.1002/jat.3596
|View full text |Cite
|
Sign up to set email alerts
|

Environmental mixture with estrogenic activity increases Hsd3b1 expression through estrogen receptors in immature rat granulosa cells

Abstract: Humans are exposed not only to single endocrine disruptors, but also to chemical mixtures that can adversely affect their reproductive health. Steroidogenesis in reproductive tissues is emerging as the key target of endocrine disruptor action. Here, we analyzed the effect of environmental chemical mixtures with estrogenic activity on steroidogenic processes in immature rat granulosa cells and whether the observed steroidogenic effects were mediated through estrogen receptors. Extracts from untreated wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…In parallel to enhanced folliculogenesis, we found that the expressions of key genes associated with both follicle development ( Creb , Ccnd2 and Inhα ) and estrogen biosynthesis ( Cyp11a1 , HSD3b1 and Cyp19a1 ) in ovaries were all significantly upregulated in rats following INHα13AA-T immunization. Of these, except for HSD3b1 in granulosa cells being directly regulated by FSH [ 28 ], the other genes were all directly FSH downstream genes [ 29 , 30 ]. In contrast, the LH target ovarian steroidogenic genes ( Star [ 31 ] and Cyp17a1 [ 32 ]), as well as pituitary Lhb expression and serum LH concentrations, were all unchanged, as was reported elsewhere [ 11 , 12 , 15 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel to enhanced folliculogenesis, we found that the expressions of key genes associated with both follicle development ( Creb , Ccnd2 and Inhα ) and estrogen biosynthesis ( Cyp11a1 , HSD3b1 and Cyp19a1 ) in ovaries were all significantly upregulated in rats following INHα13AA-T immunization. Of these, except for HSD3b1 in granulosa cells being directly regulated by FSH [ 28 ], the other genes were all directly FSH downstream genes [ 29 , 30 ]. In contrast, the LH target ovarian steroidogenic genes ( Star [ 31 ] and Cyp17a1 [ 32 ]), as well as pituitary Lhb expression and serum LH concentrations, were all unchanged, as was reported elsewhere [ 11 , 12 , 15 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the genes of interest may be crucial for steroidogenesis in porcine granulosa cells. Upregulated 3β-hydroxysteroid dehydrogenase 1 (HSD3B1) plays an important role in steroidogenesis [62]; its expression is dependent on imidacloprid [62] and estrogen [63].…”
Section: Discussionmentioning
confidence: 99%
“…The mixture-induced decrease in estradiol corresponds to upregulation of Cyp1a1, an enzyme that metabolizes estradiol (Meling et al 2020). A mixture of estrogenic extracts isolated from untreated wastewater increased expression of the steroidogenic factors Star and Hsd3B1 in cultured mouse granulosa cells (Samardzija Nenadov et al 2018). This effect was likely mediated through activation of estrogen receptors (Samardzija Nenadov et al 2018).…”
Section: F97mentioning
confidence: 92%
“…A mixture of estrogenic extracts isolated from untreated wastewater increased expression of the steroidogenic factors Star and Hsd3B1 in cultured mouse granulosa cells (Samardzija Nenadov et al 2018). This effect was likely mediated through activation of estrogen receptors (Samardzija Nenadov et al 2018). In other studies, a PBDE mixture (PBDE 47, 99, 100, and 209) was applied to co-cultured theca and granulosa cells in low (0.5; 0.25; 0.1; 0.05 ng/ mL), medium (25; 10; 4.0; 0.25 ng/mL), and high (50; 17.5; 12.5; 0.5 ng/mL) doses in short term and longterm culture periods.…”
Section: F97mentioning
confidence: 97%